The overlooked problem among surgical patients: Preoperative anxiety at Ethiopian University Hospital - Woldegerima Berhe, Yophtahe; Belayneh Melkie, Tadesse; Fitiwi Lema, Girmay; Getnet, Marye; Chekol, Wubie Birlie (Frontiers in Medicine, 2022)
Introduction Anxiety was repeatedly reported as the worst aspect of the perioperative time. The objective of this study was to assess the prevalence of preoperative anxiety among adult surgical patients at University of Gondar Comprehensive Specialized Hospital (UoGCSH), Northwest Ethiopia. Methodology A hospital-based cross-sectional study was conducted among surgical patients at the university hospital. After obtaining ethical approval, 407 surgical patients were approached during the preoperative period. Preoperative anxiety was assessed by State-Trait Anxiety Inventory. The association between variables was determined by using binary logistic regression analysis. Strength of association was described in adjusted odds ratio (AOR), and a p-value < 0.05 at 95% confidence interval was considered statistically significant. Results A total of 400 patients were included in this study with a 98.3% response rate. Preoperative anxiety was observed among 237 (59.3%) patients, and the median (IQR) STAI score was 50 (40–56.7); age, ≥ 60 years (AOR: 5.7, CI: 1.6–20.4, P: 0.007); emergency surgery (AOR: 2.5, CI: 1.3–4.7, P: 0.005); preoperative pain (AOR: 2.6, CI: 1.2–5.4, P: 0.005); and rural residency (AOR: 1.8, CI: 1.1–2.9, P: 0.031) were found significantly associated with preoperative anxiety. Conclusion The prevalence of preoperative anxiety among surgical patients was high. Older age (≥ 60 years), emergency surgery, preoperative pain, and rural residency were found significantly associated with preoperative anxiety. Assessment for preoperative anxiety should be a routine component of preoperative assessment of both elective and emergency surgical patients. Preoperative pain should be appropriately managed as it can help to reduce preoperative anxiety. Optimal anxiety reduction methods should be investigated and implemented in the hospital.